The Era of Thromboinflammation: Platelets Are Dynamic Sensors and Effector Cells During Infectious Diseases - Guo, Li; Rondina, Matthew T. (Frontiers in Immunology, 2019)
Platelets are anucleate, circulating cells produced by megakaryocytes. Platelets are the second most abundant circulating cells in the vasculature. In recent years, a robust body of literature supports the evolving role of platelets as key sentinel and effector cells in infectious diseases. Among their diverse roles, platelets are especially critical in bridging hemostatic, inflammatory, and immune continuums. Upon intravascular pathogen invasion, platelets sense and respond to viral, parasitic, and bacterial infections. In some cases, platelets directly bind to pathogens through pattern recognition receptors (PRRs) and integrin receptors or pathogen: immunoglobulin complexes through Fc and complement receptors – although our understanding of these interactions remains incomplete. Constantly scanning for areas of injury or inflammation as they circulate in the vasculature, platelets also indirectly respond to pathogen invasion through interactions with leukocytes and the endothelium. Through a diverse repertoire of mechanisms, activated platelets can directly kill pathogens, recruit leukocytes, and promote neutrophil extracellular traps (NETs) formation to facilitate pathogen clearance. At times, however, platelet activation may also be injurious to the host, exacerbating inflammation and promoting endothelial damage, coagulation, and thrombosis. There are many gaps in our understandings of the role of platelets in infectious diseases. However, with the emergence of advanced technologies, our knowledge is increasing. In the current review, we discuss these evolving roles of platelets in infectious diseases, highlighting the complex interplay of these processes with hemostatic and thrombotic pathways.